Characterization and functional analysis of two inhibitor of apoptosis genes in Zhikong scallop Chlamys farreri. (July 2016) - Miao, Guoying; Qi, Haigang; Li, Li; Que, Huayong; Zhang, Guofan
Abstract: The proteins of inhibitor of apoptosis (IAP) family play important roles in regulation of apoptosis, immunological response and cell proliferation. Here we reported two IAP genes (named CfIAP1 and CfIAP2) in Zhikong scallop Chlamys farreri . The full-length CfIAP1 cDNA contained 1552 nucleotides, encoding a predicted protein of 251 amino acids with two BIR domains. The full-length CfIAP2 cDNA contained 1243 nt, encoding a 356-aa protein with one BIR domain and one RING domain. The two genes are ubiquitously expressed in six types of tissue of C. farreri . The expression levels of CfIAP1 and CfIAP2 were significantly up-regulated after challenged with acute viral necrobiotic disease virus, lipopolysaccharide and exposure to air. Subcellular localization assay showed that CfIAP1 was mainly distributed in cytoplasm and CfIAP2 was in cytoplasm and nucleus. As assessed using a kit designed to test Caspase3 function in mammalian cells, the activity of CfCaspase3 was enhanced as a result of the down-regulation of CfIAP2 expression by dsRNA-mediated gene silencing. Our study indicated that CfIAP1 and CfIAP2 may participate in the innate immunity and stress responses and that CfIAP2 might block apoptosis via inhibiting CfCaspase3 indirectly through an unexplored mechanism in C. farreri . Highlights: The full-length cDNAs of two IAP genes were first characterized in Chlamys farreri. The two genes were ubiquitously expressed in a wide variety of tissues. The two genes are both involved in innate immunity and stress responses. CfIAP1 was probably distributed in cytoplasm and CfIAP2 was in cytoplasm and nucleus. CfIAP2 might block apoptosis via inhibiting CfCaspase3 indirectly through an undiscovered way.